Activity Pattern of Iron-Deficient Rats. Issue 5814 (10th June 1972) - Glover, J.; Jacobs, A.
Abstract : Iron-deficient rats appear to have a decrease in total activity and a disorder of diurnal rhythm. These are reversed by the administration of iron. The results may be relevant to the symptomatology of patients with iron deficiency anaemia.